(untitled) (Research, Society and Development, 2020)
The great achievements of women on the social, family and socioeconomic scale also bring to the public a picture of signs and symptoms experienced in their fertile life, which used to be between them and their gynecologists, which is the Premenstrual Tension Syndrome (STPM). The search for effective and safe alternative therapies capable of acting on the psychological and physical symptoms avoiding loss of work days and better family, social and work relationships can bring socioeconomic benefits and quality of life for women suffering from this great inconvenience. The aim of the present study was to investigate patients diagnosed with STPM with the associated use of chamomile (Matricaria recutita), apple (Malus domestica) and passion fruit (Passiflora edulis) in the 10 days prior to menstruation in tea form of said plants. For this purpose, 43 patients of childbearing age (between 18 and 49 years old) with a diagnosis of STPM in a private doctor’s office in the city of Umuarama, PR, who answered a questionnaire about the prevalence of the most frequent symptoms related to STPM, and the results observed in our study showed that the parameters: 1) Irritability and Nervousness, 2) Anxiety and 7) Increased desire for sweet eating were the most affected in relation to alternative therapy with 91%, 81% and 67%, respectively. In addition, 93% of patients reported having more than 4 in up to 10 affected parameters. This reflected the level of satisfaction with the therapy performed with 79.1% satisfaction of the women evaluated in relation to this percentage of parameters reached (91%), where the predominant age group was between 18 and 23 years of age 35% participation in said research. In this way, it was verified that the central events related to this Syndrome are the most positively affected by this proposed therapy, and that the peripheral complaints were also softened. These effects are due to the general activities of the flavonoids contained in these natural products (Passion fruit, Chamomile and Apple) acting on central receptors, similar to the activities of Gaba (gamma amino butyric acid) and its actions modulating the inflammatory process reducing the synthesis of prostaglandins and metalloproteinases respectively. Thus, it was concluded that this therapy generally improved the most frequent symptoms of this syndrome (irritability and nervousness, anxiety, and desire to eat sweets) and the quality of life of these women when using alternative therapies.